If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -2y + 2 = 0 Reorder the terms: 1 + 2 + -2y = 0 Combine like terms: 1 + 2 = 3 3 + -2y = 0 Solving 3 + -2y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2y = 0 + -3 -2y = 0 + -3 Combine like terms: 0 + -3 = -3 -2y = -3 Divide each side by '-2'. y = 1.5 Simplifying y = 1.5
| 120x-(5000-0.75x)= | | (x-1)(x-3)(x-5)(x-7)=20 | | (X-8)33=180 | | 8+n*2n=72 | | 5.4-0.103= | | 2k=p+2v | | 4x=18.8 | | 12*x=-3 | | 6x+3500=4x+4000 | | 86+2(3x-12)= | | 3(2x+1)x=-39 | | 8.3-(-2.1)= | | 5=q+12 | | 9x^3+6x^3+7= | | 120(5000-0.75x)= | | y=-16t^2+64t+8 | | .02y+.18=3 | | 0+4+4x= | | (3x-20)+(2x)=180 | | 6-9-d=3d | | 7.3+1.9y-(4.7x+5.8y)= | | Y=7*4x | | 1/2x+x= | | 0.21x-55=29 | | q^2-12q+20=0 | | -1x-5x=12 | | 2(3x+1)=15 | | 4m+6n-8+(8m-3)= | | -19=x-11 | | X=3-6*3+2 | | -4y-1=-17.25 | | x+1/2x+4+4x= |